Determination of Genetic Relatedness among Selected Rice Cultivars Using Microsatellite Markers for Cultivars Improvement through Marker Assisted Breeding - Etemad, Ali (2009)
Rice is grown in diverse environmental conditions. In this study, genetic variation among thirteen Iranian and thirteen Malaysian rice cultivars was determined using Microsatellite markers. Microsatellites are polymerase chain reaction (PCR) based and dbla ceelcuoobeoy xoed (DNA) markers which are abundant, co-dominant and widely used in various organisms. This study consisted of two parts, the first part was DNA extraction, which consisted of comparing between four different DNA extraction methods, namely the Dellaporta and CTAB as conventional methods also, Promega and Axyprep as commercial protocols kits. Comparison was also made on the effect of different leaf age as well as leaf position on different quality and yield of DNA obtained. The results of the study showed significant difference (P<0.05) between different extraction methods in relation to optical density OD 260/280 nm and DNA yield from each method. The Dellaporta method (OD260/280=2±0.07nm and DNA yield 2073±196 ng) gave the best results. The positions of different leafs (from top to bottom leaf number 4 to 1) and the ages of leafs (2, 4, 6 and 8 weeks) were also monitored for optimum DNA extraction. The results of the Duncan test showed that there was no significant difference (P>0.05) between leaf positions for 2 to 4 weeks old leaf. However, the age of leaves in young and fresh stages of tissue showed significant difference (P<0.05) in ratio of OD260/280 2±0.03 and DNA yield (1373±70 ng). The results (based on method of extraction, leaf age and position) were used for subsequent DNA extraction of the 26 rice cultivars. The second part consisted of molecular work using twenty one microsatellite primer pairs which were selected from the Gene Bank. The estimation of genetic diversity among two rice groups (Iranian and Malaysian cultivars) were done with the assistance of two softwares UVIdoc (ver.98) and POPGENE (ver.1.31). A total of 21 loci (75 alleles) were observed, of which 20 loci (95.24 %) were polymorphic, except RM338. Microsatellite loci RM1 and RM271 showed the highest polymorphism (between 94 to 136 bp in size). The Polymorphism Information Content (PIC) value was (0.578±0.170). The dendogram constructed based on genetic distance values (UPGMA) grouped the cultivars into five clusters. All of the Iranian rice cultivars were placed in cluster I and III while Malaysian rice cultivars were in clusters IV and V. However cluster II consisted of both Iranian and Malaysian rice cultivars. The results of genetic diversity among selected cultivars in this study can be used for screening of the high grain quality rice accession for backcrossing and breeding programs.